Disability Prevalence and Training Needs of Persons with Disability (PWDs) in Labo, Camarines Norte: A Bases for Extension Agenda - Angeles, Melvin; Panotes, Nicole Anne; Ferrer, Mary Jane (PT FORMOSA CENDEKIA GLOBAL, 2025)
Various agencies are collaborating to extend support to the Person-with Disability (PWD) to address different concerns and particular needs of the PWDs in the society. The present study assesses the demographic profile, disability prevalence, and training needs of the selected 71 PWDs in Labo, Camarines Norte. The results revealed that functional limitations and disability prevalence must be considered when conceptualizing the training activity. Four (4) possible training courses emerge: swine raising, organic agriculture, recycling/re-using of solid waste and indigenous, soap making, and urban or container gardening can be organized for the participants. This suggests that training should cater to the nature of the disability/special needs of PWDs. This would be the initial step for various researchers/extensionists before developing the appropriate program suited to this population group